Stabilization of Soft Soil with Rice Husk Ash on CBR Bearing Capacity and Soil Shear Strength Parameters - Hernandi, Safadzia; Desiana Vidayanti (Jurnal Teknik Sipil dan Perencanaan, 2025)
Bekasi Regency generally has an area with soft clay soil conditions, recognized as problematic soil known as expansive clay. As large-scale construction continues in the region, geotechnical issues associated with these expansive soils have become a concern. Stabilizing with additives increased the soil’s bearing capacity and shear strength. The addition of agricultural waste material, rice husk ash (RHA), is intended to improve the soil through a pozzolanic reaction. This study examines soft soil's bearing capacity and shear strength value with 5%, 10%, and 15% rice husk ash. Index properties tests comprising water content, specific gravity, grain size analysis, and Atterberg limits. Engineering properties tests comprising proctor compaction, California Bearing Ratio (CBR), and UU Triaxial. The samples cured for two days before compaction and seven days after compaction. The test results indicated that the soil was classified as CH according to USCS and A-7-6 according to AASHTO. The highest CBR and Triaxial UU test results were found with an RHA content of 15%. CBR increased by 86.44% from 4.919% to 9.172%. Cohesion value increased by 90.31% from 0.185 kg/cm2 to 0.352 kg/cm2. This study indicates that RHA could increase bearing capacity and shear strength in soil stabilization.